Relación de la Maloclusión y la Postura del Pie, en Pacientes Pediátricos Revisión Bibliográfica (2022)
Through all the bibliographic review carried out for this work, it has been determined that inadequate posture in boys and girls and malocclusions are common problems in patients in the period of growth and especially with transitional dentition, because, if the postural attitude does not is correct during growth, the muscles do not work synergistically, taking shape in the bone system in a relationship between the craniofacial morphology and the posture of the head. (Pacheco M. et al., 2021). Thus, it was sought to determine the relationship between the development of malocclusions and alterations in foot posture, in pediatric patients, through a bibliographic review, for which 50 articles from different sources of information such as Google Academics have been used. , Scielo, Scopus, Elsevier and PubMed. with inclusion criteria valid for the last 10 years and be written in Spanish or English. On the other hand, according to ethical considerations, based on Resolution No. 8430 of 1993 of the Ministry of Social Protection of Colombia, it is determined that this study is considered without risk, during data collection ethical principles are respected, such as anonymity, all information obtained is for research purposes only and will be handled solely by the researchers. This research has as ethical research principles, honesty, to develop an honest research project based on the veracity of the bibliographic sources and responsibility